GARBHADHANA SAMSKARA (PERSPEKTIF SEKS DALAM VEDA) - Ni Wayan Sumertini (Sanjiwani: Jurnal Filsafat, 2020)
Having descent in Hinduism is an obligation in Grhasta Asrama. Before entering Grhasta Asrama, the rituals of purification for the bride and groom were carried out to clean the seeds of fertilities from dirty or mala elements, so as to produce good child. Garbhadhana Samskara is one of the ritual ceremonies performed at a wedding that functions as a purification of seeds, whether kama bang or kama petak. Sex in Hinduism is sacred because it is intended to obtain offspring through the path of dharma. The purpose of Garbhadhana Samskara is to reduce the number of abortions due to less responsible sexual activity, and reduce the risk of infectious diseases due to sexual enjoyments. Garbhadhana Samskara views sex as something sacred which is based on the value of holiness and truth, without being just a slave to sexual desires. Garbhadhana Samskara is also sexuality education. The stories in Itihasa and Purana are also agree the concept of Grabhadhana where sex is sacred and time in intercourse is an important thing. The purpose of Garbhadhana Samskara is to create a descendant of the suputra who can free his parents from hell named Put. More than that, Garbhadhana Samskara created the character of satvika in children, which has a positive contribution to the empowerment of human resources.